Evaluation of the Financial Performance of Tourism Companies Traded in BIST via a Hybrid MCDM Model (International Journal of Applied Research in Management and Economics, 2020)
Tourism, the smokeless industry, has increasing importance in the development of countries because it creates added-value and employment. In Turkey, one of the World's most visited countries, the importance of this sector makes itself felt in economic crisis periods. On the other hand, in terms of investors, tourism companies always have the potential to be included in their portfolios. In this context, the aim of this study evaluates the financial performances of tourism companies publicly traded in BIST. For this purpose, the data of 2014-2018 were obtained from the Thomson Reuters Datastream database. The current ratio, quick ratio, cash ratio, debt ratio, total debt/equity ratio, net margin, return on equity, interest coverage ratio, total asset turnover, inventory turnover, and receivable turnover were used as financial ratios. The CRITIC method, one of the objective weighting methods, was applied to determine the importance level of financial ratios. A hybrid model consisting of MAUT, PROMETHEE and TOPSIS was used for evaluation of the companies. These techniques are based on different perspectives and algorithms. In this model, Borda was applied for aggregation of each techniques' ranking values. Thus, the financial performance of the tourism companies for the years 2014-2018 was evaluated more effectively. In conclusion, the company with the best financial performance is Marmaris Alt?nyunus (MAALT) in this period.